Construindo projetos, arquitetando ideias, analisando dados: a reforma curricular do curso de Licenciatura em Artes Visuais-2004/UFSM - Baptaglin, Leila Adriana (2010)
The research discussed here has been produced according to the initial training, a topic which is being reflected by me since the undergraduate course. In that time, the Graduation Program in Education - UFSM, in the line of research Education and Arts, some questions are intended to be seen in depth arising from this trajectory, this opportunity to dialogue with the critical post-curriculum studies. BUILDING PROJECTS, ARCHITECTS IDEAS, ANALYZING DATA: the curriculum reform of the graduation course in visual arts-2004/UFSM investigates: what is the impact of curricular reform in undergraduate course in visual arts-2004/UFSM/RS according to the teachers, academic course, and teachers of schools opinion, which serve as a training for students in initial training. Thus, presenting itself as a qualitative research, this study used, in addition, bibliographic and legal documents (the Pedagogical Political Project, Laws, Resolutions and Opinions) and an investigation with the two institutions involved in this process of teacher education: the university and academic institution. This study, which was held from semi-structured interviews with employees of the three sectors involved: the teachers of the School of Visual Arts Degree / UFSM while they were in a number of eight (8) teachers (4 effective and 4 substitutes), four (4) professors of visual arts in schools who were in the training of academics students during the reform in 2004 and participating in the Continuing Education Course offered by the Laboratory of Visual Arts (LAV / EC / UFSM); their academics are in the process of completion and a number of four (4) academics. From the results obtained in the investigation I prepared further interviews with each individual employee. The analysis was based on content analysis (SZYMANSKY, 2004), resulted in three stages: Pre-analysis, analytical description and interpretation of the references. These steps enabled thus verifying the design, the impact of and suggestions from different sectors facing the structuring of the curriculum of the School of Visual Arts Course in 2004 from UFSM. Taking these remarks in depth, I developed the text into categories which are: 1-Effect of increasing amount of teaching concerning teaching time: training, curriculum practices and teaching subjects in schools and in teacher training; 2 - Changes required to implement curriculum 3 - Adequacies the historical context of the curriculum, academic and local 4 - Training and bachelor's degree: generalizations and peculiarities. Therefore, from this development I realized that there is a need for adjustments in this curriculum structure. Modifications have been made, however, questions concerning the workload of teaching subjects, the adequacy of the curriculum to local needs relating to both space and culture and preparation of teachers who will work in the training of future teachers, are issues that still deserve our attention. However, it is not only training institution in which we should hold, I realized that the school apply some points that hinder the work and dedication of the professional. Linking these two institutions and provide for training the "correct" through many changes and a joint performance of the sectors involved in this process. These changes are necessary and highly significant in the contemporary context, because what is good and sufficient enough today is not necessarily effective tomorrow.